Infotainment Media Forms Hybrid Genres in the American and Romanian Televisual Press - BOGDAN (Nicoară), Rada Daniela (Presa Universitară Clujeană, 2021)
The hypothesis of this thesis is that the 21st century has redefined journalism by the subjectivity with which several topics of national interest are addressed. Following the American model and considering the era of globalization we live in, the initial principles of journalism are considerably losing their importance, converging to entertainment. We shall approach the problem of genre hybridization within the televisual press, insisting upon the emergent forms proposed by some American (The Daily Show, Last Week Tonight, The Late Night and Late Show) and Romanian shows (România de la A la Z, Starea Nației, Lumea lui Banciu and În gura presei. Hence, all these case studies plan to emphasize the conjunction of some serious and non-serious genres, in an attempt to define the variable forms of an “ongoing journalistic genre” (infotainment).